What is the best treatment for recurrent methicillin‐resistantStaphylococcus aureusskin and soft tissue infections?. Issue 12 (December 2017) - Anderson, Carrie
Abstract : EVIDENCE‐BASED ANSWER : For patients with colonized methicillin‐resistant S aureus (MRSA), chlorhexidine wash, nasal mupirocin, oral rifampin, and oral doxycycline doubles decolonization rates compared with no treatment (SOR: B, small RCT), while a similar regimen of nasal mupirocin, hexachlorophene wash, and oral antibiotics is associated with a marked reduction in the recurrence rate of MRSA infections (SOR: C, small prospective cohort). Mupirocin plus chlorhexidine is no better than chlorhexidine alone for decolonization (SOR: B, small RCT). Recurrent infections may be treated with decolonization therapy with mupirocin with or without topical antiseptic solution or dilute bleach baths (SOR: C, expert opinion).